ANALISIS BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PADA PERUSAHAAN SEKTOR KESEHATAN DI BURSA EFEK INDONESIA (BEI) - Dita Putri Puspita; Dyah Shinta Kusumaningtyas; Ade Irawan (The Asia Pacific Journal Of Management Studies, 2025)
This study aims to analyze the financial performance of the healthcare sector listed on the Indonesia Stock Exchange (IDX) including PT Medikaloka Hermina Tbk (HEAL), PT Siloam International Hospitals Tbk (SILO), PT Mitra Keluarga Karyasehat Tbk (MIKA), PT Sejahtera Anugrahjaya Tbk (SRAJ), PT Famon Awal Bros Sedaya Tbk (PRAY), PT Sarana Meditama Metropolitan Tbk (SAME), PT Metro Healthcare Indonesia Tbk (CARE) using the Balanced Scorecard method. measured using indicators from each perspective, such as the financial perspective is measured by the ROA, ROE, and Net Profit Margin (NPM) indicators. The Customer Perspective is measured by cash receipts from customers. The Internal Business Process Perspective is measured using the company's Operating Profit. Finally, the Growth and Learning Perspective is measured using Income/Employee. This study uses a Descriptive quantitative method and the data used in this study is secondary data from the annual financial reports of each company for the period 2021-2024. The results of this study indicate that the assessment of hospital management performance in the financial perspective is measured using the Net Profit Margin (NPM), ROE and ROA ratios, overall the scorecard assessment has decreased so that it is categorized as poor performance. From the customer perspective, the company's overall cash is considered very good. In the internal business process perspective, it has also been assessed as good. And in the growth and learning perspective, growth and learning as a whole are considered less good.